Conceptualizing a Human Right to Prevention in Global HIV/AIDS Policy - Meier, Benjamin Mason (Oxford University Press, 2012)
Given current constraints on universal treatment campaigns, recent advances in public health prevention initiatives have revitalized efforts to stem the tide of HIV transmission. Yet, despite a growing imperative for prevention—supported by the promise of behavioral, structural and biomedical approaches to lower the incidence of HIV—human rights frameworks remain limited in addressing collective prevention policy through global health governance. Assessing the evolution of rights-based approaches to global HIV/AIDS policy, this review finds that human rights have shifted from collective public health to individual treatment access. While the advent of the HIV/AIDS pandemic gave meaning to rights in framing global health policy, the application of rights in treatment access litigation came at the expense of public health prevention efforts. Where the human rights framework remains limited to individual rights enforced against a state duty bearer, such rights have faced constrained application in framing population-level policy to realize the public good of HIV prevention. Concluding that human rights frameworks must be developed to reflect the complementarity of individual treatment and collective prevention, this article conceptualizes collective rights to public health, structuring collective combination prevention to alleviate limitations on individual rights frameworks and frame rights-based global HIV/AIDS policy to assure research expansion, prevention access and health system integration.